Vaccine uptake and associated factors in an irregular urban settlement in northeastern Brazil: a cross-sectional study - Ana Amélia Corrêa de Araújo Veras; Eduardo Jorge da Fonseca Lima; Maria de Fátima Costa Caminha; Suzana Lins da Silva; Amanda Alves Moreira de Castro; Andressa Lílian Bezerra Bernardo; Maria Lídia Amaral Barbosa Ventura; Pedro Israel Cabral de Lira; Malaquias Batista Filho (BMC, 2020)
Abstract Background Globally, childhood immunization saves the lives of 2-3 million children annually by protecting them against vaccine-preventable diseases. In 2017, 116.2 million children were vaccinated worldwide according to the World Health Organization. Nevertheless, figures suggest that 19.5 million children around the world fail to receive the benefits of complete immunization. Methods This cross-sectional study analyzed vaccine uptake and the factors associated with incomplete vaccination schedule in children of up to 36 months of age assisted by the family health strategy in an irregular settlement located in a state capital city in northeastern Brazil. This study was nested within a larger study entitled "Health, nutrition and healthcare services in an urban slum population in Recife, Pernambuco", conducted in 2015. A census included 309 children, with vaccination data obtained, exclusively, from their vaccination cards records. An ad hoc database was constructed with variables of interest. Absolute and relative values were calculated for the socioeconomic, demographic, obstetric and biological data. To identify possible factors associated with incomplete vaccination schedule, crude and multivariable Poisson regression analyses were performed, and conducted in accordance with the forward selection method with robust variance and the adjusted prevalence ratio was calculated with the 95% CI. Variables with p-values < 0.20 in the unadjusted stage were included in the multivariable analysis. The statistical significance of each variable was evaluated using the Wald test, with p-values < 0.05. Results Just half of the children (52,1%) was classified as complete vaccination schedule. In the final model, the factors associated with incomplete vaccination schedule were age 12-36 months and the mother who did not complete high school. Conclusion The percentage of vaccine uptake found was far below the recommendation of the National Childhood Immunization Schedule and was associated with child's age and mother's education level. Based on these findings, the family healthcare teams may elaborate vaccination strategies aimed at reaching the coverage rates established by the national immunization program. Optimizing coverage will ultimately prevent the resurgence, at epidemic level, of infectious diseases that are already under control in this country.